2007
DOI: 10.1063/1.2408646
|View full text |Cite
|
Sign up to set email alerts
|

Awaking of ferromagnetism in GaMnN through control of Mn valence

Abstract: Room temperature ferromagnetism of GaMnN thin films is awaked by a mild hydrogenation treatment of samples synthesized by molecular beam epitaxy. Local environment of Mn atoms is monitored by Mn-L2,3 near edge x-ray absorption fine structure (NEXAFS) technique. Doped Mn ions are present at substitutional sites of Ga both before and after the hydrogenation. No secondary phase can be detected. Major valency of Mn changes from +3 to +2 by the hydrogenation. The present result supports the model that the ferromagn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 5 publications
1
22
1
Order By: Relevance
“…5 indicate the paramagnetic behavior of films A, B, and C. Therefore, the magnetic properties of the Mn-doped GaN films are not dependent on the valence of Mn ions. This finding is different from previous theoretical prediction [36] and experimental reports [3,6], where ferromagnetism is scaled with the Mn 3+ . However, the paramagnetism of the films in the present study is 3+ .…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…5 indicate the paramagnetic behavior of films A, B, and C. Therefore, the magnetic properties of the Mn-doped GaN films are not dependent on the valence of Mn ions. This finding is different from previous theoretical prediction [36] and experimental reports [3,6], where ferromagnetism is scaled with the Mn 3+ . However, the paramagnetism of the films in the present study is 3+ .…”
Section: Resultscontrasting
confidence: 85%
“…For instance, ferromagnetism occurs in GaN:Mn with Mn 3+ but disappears when Mn 3+ changes to Mn 2+ [2][3][4][5]. Nevertheless, Sonoda et al [6] reported that the coexistence of Mn 2+ and Mn 3+ is a basis of ferromagnetism. In addition, the valence of Mn ions exerts much influence on the optical properties of GaN:Mn.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…It is known that doping with transition metals influences the electronic and magnetic properties of NWs. Experimental work reported on the synthesis of GaMnN material exhibits ferromagnetism at room temperature and depended on the concentration of impurities . Mn ions were present in substitutional sites of Ga ion for both before and after hydrogenation .…”
Section: Introductionmentioning
confidence: 99%
“…Experimental work reported on the synthesis of GaMnN material exhibits ferromagnetism at room temperature and depended on the concentration of impurities . Mn ions were present in substitutional sites of Ga ion for both before and after hydrogenation . Gao et al successfully synthesized room‐temperature GaMnN film using a laser molecular beam epitaxial method, whose structural and magnetic properties are strongly dependent on the substrate temperature.…”
Section: Introductionmentioning
confidence: 99%